From Residential Care to Supportive Housing for People With Psychiatric Disabilities: Past, Present, and Future - Farkas, Marianne; Coe, Steve (Frontiers in Psychiatry, 2019)
For centuries, treatment and accommodation for people with significant mental health conditions in many countries, including the United States, have been viewed as necessarily inseparable elements, first in asylums and then, with deinstitutionalization, in community care models. The advent of psychiatric rehabilitation and later, recovery, helped to shift the paradigm of mental health services and the role of housing, to one focused on promoting the ability of individuals to achieve not only a life located in the community, but one that reflects a meaningful life as part of a community. In this context, supportive housing emerged as a model based on integrated, permanent, affordable housing, selected by the person, with flexible supports that are functionally separate, but available as needed and wanted. This model of housing has been predominant in American mental health services for over 20 years and evidence now exists for its outcomes in terms of housing stability, symptom reduction and psychosocial variables. Current challenges both at the societal and the individual level, confront the sustainability of supportive housing, with some efforts being made by housing groups to address these challenges. This article reviews the evolution of supportive housing and its basic tenets, identifying the challenges and some efforts to address them. In addition, the article discusses the current social and economic climate, which appears to be shaping opposing trends, and makes a call to action, to mitigate the possible risks to the future of this value-based housing approach.